Does Side of Onset Influence the Pattern of Cerebral Atrophy in Parkinson’s Disease? - Santos, Maria C. A.; Campos, Lidiane S.; Guimarães, Rachel P.; Piccinin, Camila C.; Azevedo, Paula C.; Piovesana, Luiza G.; De Campos, Brunno Machado; Scarparo Amato-Filho, Augusto C.; Cendes, Fernando; D’Abreu, Anelyssa (Frontiers in Neurology, 2016)
Background: Several neuroimaging studies revealed widespread neurodegeneration in Parkinson's disease but only few considered the asymmetrical clinical presentation. Objective: To investigate gray matter (GM) atrophy in Parkinson Disease considering the side of motor symptom onset. Methods: Sixty patients (57.87± 10.27 years) diagnosed according to the Brain Bank criteria, 26 with right-sided disease onset (RDO) and 34 with left-sided disease onset (LDO), were compared to 80 healthy controls (HC) (57.1± 9.47 years). T1-weighted images were acquired on a 3T scanner. VBM8 (SPM8/Dartel) on Matlab R2012b platform processed and analyzed the images. Statistics included a two-sample test (FWE p<0.05) with extent threshold of 20 voxels. In a secondary analysis, we used MRIcro software to flip the images right/left of 25 patients, which had a RDO, so that all images had the contralateral side of disease onset at the right hemisphere. Thirty-five HC images were flipped, as the hemispheres are not completely equivalent. Results: Compared to HC, GM atrophy in LDO was identified in the insula, putamen, anterior cingulate, frontotemporal cortex and right caudate. For the RDO group, anterior cingulate, insula, frontotemporal and occipital cortex. VBM of total brain-flipped images showed GM loss mainly in the left putamen, left olfactory cortex, amygdala, parahipocampal gyrus and in the rectus gyrus, insula, frontotemporal cortex, cuneus, precuneus and calcarine fissure bilaterally. (p<0.05 FWE corrected). Conclusions: The study revealed widespread GM atrophy in PD, predominantly in the left hemisphere. Future investigations should also consider handedness and side of onset to better characterize cerebral involvement and its progression in PD.